Automation-Induced Complacency Potential: Development and Validation of a New Scale - Merritt, Stephanie M.; Ako-Brew, Alicia; Bryant, William J.; Staley, Amy; McKenna, Michael; Leone, Austin; Shirase, Lei (Frontiers in Psychology, 2019)
Complacency, or sub-optimal monitoring of automation performance, has been cited as a contributing factor in numerous major transportation and medical incidents. Researchers are working to identify individual differences that correlate with complacency as one strategy for preventing complacency-related accidents. Automation-induced complacency potential is an individual difference reflecting a general tendency to be complacent across a wide variety of situations which is similar to, but distinct from trust. Accurately assessing complacency potential may improve our ability to predict and prevent complacency in safety-critical occupations. Much past research has employed an existing measure of complacency potential. However, in the 25 years since that scale was published, our conceptual understanding of complacency itself has evolved, and we propose that an updated scale of complacency potential is needed. The goal of the present study was to develop, and provide initial validation evidence for, a new measure of automation-induced complacency potential that parallels the current conceptualization of complacency. In a sample of 475 online respondents, we tested 10 new items and found that they clustered into two separate scales: Alleviating Workload (which focuses on attitudes about the use of automation to ease workloads) and Monitoring (which focuses on attitudes toward monitoring of automation). Alleviating workload correlated moderately with the existing complacency potential rating scale, while monitoring did not. Further, both the alleviating workload and monitoring scales showed discriminant validity from the previous complacency potential scale and from similar constructs, such as propensity to trust. In an initial examination of criterion-related validity, only the monitoring-focused scale had a significant relationship with hypothetical complacency (r = -.42, p < .01), and it had significant incremental validity over and above all other individual difference measures in the study. These results suggest that our new monitoring-related items could be used as a measure of automation-induced complacency potential and, compared with similar scales, this new measure may have unique value in predicting complacent behavior.